Encountering ‘Broken’ Public Services: Defiance and Disaffection at the Frontlines of the Democratic State - John Boswell (The Political Quarterly, 2026)
Abstract The apparently parlous state of public services in advanced liberal democracies has become a hot topic, nowhere more so than in ‘broken Britain’. Indeed, there is much debate in both politics scholarship and political rhetoric about the nature and causes of this decline, and its potential remedies. All perspectives are at pains to characterise everyday citizens as meek victims of failing public services. But this characterisation is too simplistic. Citizens do not always meekly accept what they are served: they can and often do exercise agency as they navigate and negotiate the frontline implementation of laws, policies, programmes and services. In this article, I reflect on what those forms of frontline agency entail, what they mean for how we understand the dynamics of democratic disaffection, and what that understanding means for how we might pursue democratic reform.